Socio-demographic and clinical profile of sudden natural deaths in South Mumbai, India - Chaudhari, Vinod Ashok; Mohite, Shailesh C. (International Journal of Research in Medical Sciences, 2017)
Background: Sudden and unexpected death from the natural disease has been of continuing interest to the medical profession. The aim was to study the socio-demographic and clinical profile of sudden natural deaths, in South Mumbai, India. Methods: Prospective and descriptive study of sudden natural deaths (SND) whose autopsy conducted in the department of Forensic Medicine and Toxicology, Topiwala National Medical College and Hospital, Mumbai from 1st September 2006 to 31st August 2009. Results: The total of two hundred thirty SND studied during the study period of three years. The proportion of affected female cases was same as that of a male in each system. Male to female ratio in cardiovascular system, respiratory system, gastrointestinal system, central nervous system, and genitourinary system were 4.75:1, 6.20:1, 8:1, 7:2 and 1:2 respectively. The most of the victims were from Mumbai city (67.83%), followed by Mumbai suburban (23.91%). The maximum number of cases had primary level (27.39%) education. The most common terminal sign and symptoms of SND were unconsciousness (32.61%), followed by chest pain (22.61%). The common place of onset of terminal signs and symptoms of SND were home (44.78%). The most of the deaths seen in monsoon (June-September: 40%), followed by summer (Feb-May: 30.43%). Conclusions: Proper health education and awareness among the people regarding sudden natural death. We emphasize to reduce the deaths by emergency services and early transportation of the cases after identifying clinical signs.